Komodifikasi Personal Branding di Media Sosial Dokter Mutiara Sangaji - Wulandari Wurjanti (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Doctors act as producers and consumers of health content that not only serves to disseminate health information, but also to build personal credibility, attract patients, and educate the public through social media. This study focuses on the Instagram account @mutiarasangaji owned by Doctor Mutiara Sangaji, a nutritionist who uses this platform to share her personal and professional experiences, including her life journey in implementing a healthy lifestyle and overcoming Peripartum Cardiomyopathy (PPCM). This study uses a qualitative description method and consists of 3 stages, namely data reduction, data presentation, and drawing conclusions. By focusing on the eight personal branding concepts of Peter Montoya through content analysis and the application of personal branding concepts, this study shows that Doctor Mutiara has succeeded in building a strong self-image by utilizing life experiences as her personal branding "commodity" to attract the attention of her audience. By applying the eight laws of personal branding on her Instagram, this Instagram account is not only a source of health information, but also an effective marketing tool to increase credibility and expand patient networks.